2020
DOI: 10.1177/1550059420914200
|View full text |Cite
|
Sign up to set email alerts
|

MMN-Indexed Auditory Change Detection in Major Depressive Disorder

Abstract: In major depressive disorder (MDD), event-related potentials that are involved in auditory cortex function (i.e. N100 and P300) often have greater latencies and decreased amplitudes. The auditory mismatch negativity (MMN) is thought to be produced by generators in the auditory cortex, as well as the frontal lobes. Reports on differences in MMN in those with MDD have been varied. It was hypothesized that the wide range of results in the literature may be due to the use of different deviant types in eliciting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
1
12
0
3
Order By: Relevance
“…Certain studies in MDD populations have found reduced (i.e. decreased amplitude, Qiao et al, 2013;Takei et al, 2009) as well as increased (Bissonnette et al, 2020;He et al, 2010;Kähkönen et al, 2007;Restuccia et al, 2016) MMN amplitudes, and longer latencies (Bissonnette et al, 2020;Qiao et al, 2013). A recent study also identified a potential link between MMN amplitude and functional outcomes in MDD patients (Kim et al, 2020).…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 95%
“…Certain studies in MDD populations have found reduced (i.e. decreased amplitude, Qiao et al, 2013;Takei et al, 2009) as well as increased (Bissonnette et al, 2020;He et al, 2010;Kähkönen et al, 2007;Restuccia et al, 2016) MMN amplitudes, and longer latencies (Bissonnette et al, 2020;Qiao et al, 2013). A recent study also identified a potential link between MMN amplitude and functional outcomes in MDD patients (Kim et al, 2020).…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 95%
“…They found that first-episode patients had lower MMN amplitudes compared to healthy controls, while no differences were found between the recurrent and firstepisode groups. A similar experimental procedure was used by Bissonnette et al[88] to compare MMN amplitudes between MDD patients and healthy subjects. However, MDD and BD groups did not significantly differ from healthy subjects.…”
mentioning
confidence: 99%
“…Functionally, the MMN latency represents the point at which the distinction between the standard and deviant stimuli is registered, which adds in a much stronger dependency on the generation of the early and midcomponents of the standard and deviant auditory evoked potentials. There is a litany of factors linked with changes in latency, including stimulus presentation rate, 79 complexity of the stimuli, 80 and cognitive ability. 81 In the context of the Schmidt model, 40 this would point at changes in the flexibility of the PAC to adapt to incoming neural signals.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…As is to be expected, based on the history of the MMN findings described thus far, there remains significant variation in the symptom correlations associated with the paradigm used. Bissonnette et al 79 found a significant negative correlation between the location-deviant MMN amplitude and the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D), whereas Naismith et al 96 noted a correlation between pitch-deviant MMN amplitude and semantic fluency scores. It should be noted that in the latter of these examples, the MMN amplitudes were taken from temporal cortex electrodes in late-life depression patients, which raises the possibility that this correlation is driven by age-related deterioration, comorbid mild cognitive impairment, or both.…”
Section: Patient Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation